2020
DOI: 10.3390/ijerph18010035
|View full text |Cite
|
Sign up to set email alerts
|

Are There Differences in Concentric Isokinetic Strength Perfor-Mance Profiles between International and Non-International Elite Soccer Players?

Abstract: The purpose of this study is to evaluate the differences in concentric isokinetic strength characteristics of the knee extensor and knee flexor musculature between international (IL) and non-international level (N-IL) soccer players. The second aim is to establish strength symmetry status in knee muscles for dominant (DL) and non-dominant (NDL) legs for both within and between groups. 100 male top elite soccer players (IL: n = 36, age = 27.5 ± 3.4 years and N-IL: n = 64, age = 27.7 ± 6.4 years) underwent conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…Additionally, Chiaia et al reported that mean hip abductor torques demonstrated no difference between dominant and NDLs in elite female soccer players [31]. Sliwowski et al also reported an increase in symmetry of muscle strength at the international level when compared to the non-international level [30], which may have been influenced by the fact that the subjects in the present study were relatively young although at the elite level. Although asymmetry of muscle strength in the lower extremities and H/Q ratio has been reported to be a risk factor for several sports injuries, muscle strength differs between DLs and NDLs in soccer players clinically relevant information to know to enhance injury prevention.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Additionally, Chiaia et al reported that mean hip abductor torques demonstrated no difference between dominant and NDLs in elite female soccer players [31]. Sliwowski et al also reported an increase in symmetry of muscle strength at the international level when compared to the non-international level [30], which may have been influenced by the fact that the subjects in the present study were relatively young although at the elite level. Although asymmetry of muscle strength in the lower extremities and H/Q ratio has been reported to be a risk factor for several sports injuries, muscle strength differs between DLs and NDLs in soccer players clinically relevant information to know to enhance injury prevention.…”
Section: Discussionmentioning
confidence: 45%
“…There are several reports on the differences in muscle strength between DL and NDL or muscle strength asymmetry. Sliwowski et al reported that knee extension and flexion in the DL were stronger than in the NDL in male elite soccer players [30]. On the other hand, DeLang et al reported no asymmetry in muscle strength in all of the periarticular hip, knee extensor, and knee flexor muscles in male college soccer players [21].…”
Section: Discussionmentioning
confidence: 99%
“…At this age, soccer players have not yet reached their maximum level of motor abilities. However, the magnitude of muscle torque also depends on the sports skill level [ 35 , 36 , 57 ]. Relatively low values of knee joint torques may also result from general training, which was mainly carried out without a strong focus on lower limb strength.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, speed and jumping abilities are crucial in decisive match situations in soccer. Moreover, it was reported that a higher H/Q ratio is associated with longer professional training [ 35 ] and higher sports skills in soccer [ 27 , 36 ]. This may lead one to ask whether a higher H/Q ratio, which is favorable for preventing hamstring strain and ACL injuries, will also be beneficial for the performance of sprinting and jumping tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Isokinetic knee muscle strength performance data were collected as previously described in Śliwowski et al (2017) and Śliwowski et al (2021) .…”
Section: Methodsmentioning
confidence: 99%